2016
DOI: 10.1073/pnas.1509834113
|View full text |Cite
|
Sign up to set email alerts
|

Extracardiac septum transversum/proepicardial endothelial cells pattern embryonic coronary arterio–venous connections

Abstract: Recent reports suggest that mammalian embryonic coronary endothelium (CoE) originates from the sinus venosus and ventricular endocardium. However, the contribution of extracardiac cells to CoE is thought to be minor and nonsignificant for coronary formation. Using classic (Wt1 Cre ) and previously undescribed (G2-Gata4 Cre ) transgenic mouse models for the study of coronary vascular development, we show that extracardiac septum transversum/ proepicardium (ST/PE)-derived endothelial cells are required for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
126
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(130 citation statements)
references
References 30 publications
2
126
1
1
Order By: Relevance
“…24 However, Cre-based lineage tracing in mouse studies showed that at most a small fraction of coronary vascular ECs arise from (pro)epicardium. 6,[28][29][30][31][32] In this study, although a few epicardial cells were labeled by Npr3-CreER, Npr3 + cells (including Npr3 + epicardial cells) minimally contributed to coronary vessels in the ventricular free walls. Taken together, our data are consistent with previous work suggesting the SV as the major source for coronary vessels in the ventricular free walls.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…24 However, Cre-based lineage tracing in mouse studies showed that at most a small fraction of coronary vascular ECs arise from (pro)epicardium. 6,[28][29][30][31][32] In this study, although a few epicardial cells were labeled by Npr3-CreER, Npr3 + cells (including Npr3 + epicardial cells) minimally contributed to coronary vessels in the ventricular free walls. Taken together, our data are consistent with previous work suggesting the SV as the major source for coronary vessels in the ventricular free walls.…”
Section: Discussionmentioning
confidence: 57%
“…[5][6][7][8]14,[23][24][25][26][27] A consensus has emerged that there are 3 important sources for coronary vessels: proepicardium, VE, and SV. [1][2][3][4]28 Each source represents a unique developmental origin that may determine different models of coronary vessels formation. However, there is controversy over whether VE or SV is the major source for most coronary vessels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the same study revealed that the vessel density in matrigel plugs after subcutaneously injection, in mice lacking WT1 expression in endothelial cells, is significantly reduced compared to wild-type animals (71). Furthermore, deletion of WT1 in endothelial cells resulted in major reduction in cardiac vessel formation during mouse cardiac development supporting the presence of WT1 and the essential role of WT in cardiac endothelial cells (86).…”
Section: The Role Of Wt1 In Endothelial Cellsmentioning
confidence: 82%
“…Lineage-marked descendants of mesothelium from multiple organs have been isolated and shown to have a similar potency to epicardium-derived cells (EPDCs) (Rinkevich et al, 2012). While there is some debate about the degree to which EPDCs contribute to the endothelium of the coronary vasculature (Pennisi, 2016), several studies indicate some contribution of the epicardium lineage to arterial vessels with the remainder coming from other sources (Cano et al, 2016; Chen et al, 2014a; Katz et al, 2012; Palmquist-Gomes et al, 2018; Pérez-Pomares and de la Pompa, 2011). Whether this endothelial contribution comes from EPDCs or another epicardial subtype is currently not known.…”
Section: Discussionmentioning
confidence: 99%